2004
DOI: 10.1080/03079450310001610613
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of goose circovirus infection in Hungarian geese samples using polymerase chain reaction and dot blot hybridization tests

Abstract: A polymerase chain reaction (PCR) and dot blot hybridization (DBH) test have been developed for the diagnosis of infection by a novel circovirus of geese (GoCV). These tests were applied to samples of bursae of Fabricius from sick and dead birds from commercial goose farms in Hungary. In this second report of the occurrence of circovirus infection in diseased geese, 103 of 214 (48.1%) and 37 of 150 (24.6%) birds, and 49 of 76 (64.5%) and 18 of 76 (23.7%) flocks were positive by PCR and DBH respectively. The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 19 publications
1
32
0
2
Order By: Relevance
“…These infections are now widely accepted as being highly significant, and therefore similar findings in geese raise the possibility that GoCV infection may well have clinicopathological significance. Since it has recently been shown that circovirus infection is widespread in farmed geese (Ball et al ., 2004), there is clearly a need for further work to accurately establish the significance of this infection. In conclusion, a sensitive and specific method of detecting goose circovirus DNA in formalin-fixed paraffin-embedded tissues has been developed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These infections are now widely accepted as being highly significant, and therefore similar findings in geese raise the possibility that GoCV infection may well have clinicopathological significance. Since it has recently been shown that circovirus infection is widespread in farmed geese (Ball et al ., 2004), there is clearly a need for further work to accurately establish the significance of this infection. In conclusion, a sensitive and specific method of detecting goose circovirus DNA in formalin-fixed paraffin-embedded tissues has been developed.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Hungarian geese flocks diagnosed as infected by polymerase chain reaction (PCR) or dot blot hybridization were compared with non-infected flocks. With the exception of circovirus inclusions, which were found in the BF of birds in three infected flocks, no particular clinical syndrome or laboratory findings could be specifically associated with circovirus infection (Ball et al ., 2004). Thus, there is a need for further studies to establish the role, if any, of circoviruses in disease in geese.…”
Section: Introductionmentioning
confidence: 99%
“…The PCR products were separated by electrophoresis on a 2% (w/v) of agarose gel and the DNA bands were stained with ethidium bromide (0.5 mg/ml) and visualized using ultraviolet light. The specificity of the test was evaluated by applying the PCR test to known GoCV-positive and PiCV-positive samples of BF (Todd et al ., 2002;Ball et al ., 2004), respectively. SYBR Green real-time PCR test.…”
Section: Methodsmentioning
confidence: 99%
“…This paper describes the first development of a PCR test for diagnosing DuCV infections and its use in assessing the prevalence of circovirus infections in dead and sick ducks. In the absence of serological tests, PCR has proved to be a specific and sensitive method for diagnosing avian circovirus infections (Ypelaar et al ., 1999;Todd et al ., 2002;Ball et al ., 2004). However, its ability to detect circovirus DNA in clinically normal birds, for example pigeons (Todd et al ., 2002), suggests that while it may be useful for diagnosing circovirus infections, PCR may be too sensitive to use as a diagnostic of disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation